The Linguistic Construction of Associative Personal Labelization of Facebookers’ Nicks - Azhar, Iqbal Nurul; Hikmah, Darul (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2020)
This study investigates nicks (nicknames) of Facebook users (Facebookers). It specifically reveals the process of how Facebookers associate themselves with their nicknames and with all things around them. This study also finds out the factors that contribute to the choice of Facebookers to use their nicknames. This study uses sociolinguistic to approach the data. The data were obtained by using content analysis method. The data analysis method used to analyze the data was the Correlation Method with referents as the determining elements. The result of the study shows that there are personal identities associated to the nicknames used by Facebook users. It also shows that the uses of the nicknames by the Facebook users are influenced by their personal fancies (personal labelization). Besides, there are fifteen factors contributing to the choices of nicks (nicknames) by Facebook users, five major reasons that caused the informants to create the unique nicks and three issues which can be summarized related to personal autolabelization phenomena.